Analysis of determining customer priority complaints by using Analytic Hierarchy Process (AHP) techniques in PDAM Tirtauli Pematangsiantar - Eka Desriani Aritonang; Agus Perdana Windarto; Wida Prima Mustika (IJISTECH (International Journal of Information System and Technology), 2020)
The purpose of this study is to analyze the priority determination of customer complaints by using ranking techniques in decision support systems. Data sources were obtained from PDAM Tirtauli Pematangsiantar by conducting interviews and direct observation. Data obtained directly at PDAM Tirtauli Pematangsiantar. The technique used is the AHP (Analytical Hierarchy Process) method. The assessment criteria used are: Dead Air (K1), Pipeline Damage (K2), Customer Damage Pipeline (K3) and Damage Meter (K4). The results of the study were obtained from 4 criteria, obtained "Dead Water" (K1) with a value (0.502) as the first rank, and "Service pipe damage" (K2) as the second rank.